Sensitive detection of gene expression in mycobacteria under replicating and non-replicating conditions using optimized far-red reporters. - Paul Carroll; Lise J Schreuder; Julian Muwanguzi-Karugaba; Siouxsie Wiles; Brian D Robertson; Jorge Ripoll; Theresa H Ward; Gregory J Bancroft; Ulrich E Schaible; Tanya Parish (PLoS ONE)
Fluorescent reporter proteins have proven useful for imaging techniques in many organisms. We constructed optimized expression systems for several fluorescent proteins from the far-red region of the spectrum and analyzed their utility in several mycobacterial species. Plasmids expressing variants of the Discosoma Red fluorescent protein (DsRed) from the Mycobacterium bovis hsp60 promoter were unstable; in contrast expression from the Mycobacterium smegmatis rpsA promoter was stable. In Mycobacterium tuberculosis expression of several of the far-red reporters was readily visualised by eye and three reporters (mCherry, tdTomato, and Turbo-635) fluoresced at a high intensity. Strains expressing mCherry showed no fitness defects in vitro or in macrophages. Treatment of cells with antibiotics demonstrated that mCherry could also be used as a reporter for cell death, since fluorescence decreased in the presence of a bactericidal compound, but remained stable in the presence of a bacteriostatic compound. mCherry was functional under hypoxic conditions; using mCherry we demonstrated that the P(mtbB) is expressed early in hypoxia and progressively down-regulated. mCherry and other far-red fluorescent proteins will have multiple uses in investigating the biology of mycobacteria, particularly under non-replicating, or low cell density conditions, as well as providing a novel means of detecting cell death rapidly.